"The non-other" of Nicolas of Cusa and its theoretical potential for the history of philosophy - Александрова, А. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article analyses the two approaches of interpretation of "non-other" of Nicholas of Cusa in philosophical studies of O.Losyev and G. Shtal.